Transnational Feminist Solidarity in Action: The Case of Sisters Uncut and Palestinian Women - Eunike Zefanya (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study examines the advocacy strategies used by Sisters Uncut, a feminist grass-root group based in the United Kingdom, in supporting Palestinian women during the period of 2021–2025. The research is driven by the structural and intersecting forms of oppression experienced by Palestinian women, including from state violence and gender-based violence which have intensitified with the escalation of the Israel-Palestine conflict. Sisters Uncut demonstrates a significant expansion of its advocacy agenda, extending beyond domestic issues to international solidarity through direct-action tactics conducted both in physical public spaces and digital platforms. This research applies New Social Movement theory to explain the characteristics of Sisters Uncut’s movement as a part of contemporary feminist movement. Furthermore, the concept of Intersectional Feminism is employed to analyse the multiple layers of oppression faced by Palestinian women. The study also utilises the Transnational Advocacy Network framework to examine the cross-border advocacy strategies of Sisters Uncut that focuses on four main tactics: information politics, symbolic politics, leverage politics, and accountability politics. This research employs a qualitative descriptive method with library research as the primary data collection approach. The findings reveal that Sisters Uncut actively expands its campaign beyond national borders, actively engaging in transnational feminist solidarity by advocating for the protection of Palestinian women through various advocacy strategies.